Liquid crystalline drug delivery systems - Nalone, Luciana (2020)
Liquid crystals (LCs) were discovered in 1888 by Austrian botanist Friedrich Reinitzer (1888). The crystalline liquid system combines the properties of the solid and liquid states simultaneously, thus presenting a mesomorphic state. It can be defined as a positively disordered solid or an orientationally ordered liquid, thus combining the optical and electrical anisotropy of a solid with the mobility and fluidity of a liquid. It has gained attention because it may have the capability to both enhancing solubility and controlling drug release rate. LCs are easy to produce, biocompatible, cheap, and stable. This type of system promotes the controlled release of active substances, increased potency, and pharmacological efficacy in living organisms. Given this, this chapter explores the use of LCs for drug delivery systems.